Analysis of the cavebath of Miskolctapolca’s brand elements and guests satisfaction - Anetta Müller; Eszter Judit Boda; Gergely Ráthonyi; Kinga Ráthonyi-Ódor; Barbara Barcsák; Erika Könyves; Melinda Bíró; Beáta Dobay; Elena Bendíkova (Apstract: Applied Studies in Agribusiness and Commerce, 2016)
In the region of Northern Hungary the unique Cavebath of Miskolcatapolca is one of the leading health tourism service positioning itself on national and international market with its developing supply items and 4 star qualifications. It has a unique natural background all over in Europe; this uniqueness gives an opportunity to develop brand, which is a determinative item of competitiveness. Because of the competition between destinations and the ever-changing nature of tourists’ expectations and behavior tourism destinations need to be managed as other commercial brands. The aim of our research was to analyze the role and possibilities of product development which is based on the unique natural factors, and to help to expand the domestic health tourism supply. We examined how the possibility of branding and brand equity change based on brand elements; how satisfied are guests with the services; how often guests visit the bath; what kind of period guests arrive in the bath; what kind of services do guests try; how do guests arrive in the bath with. In summer of 2014 we asked 210 Hungarian customers to fill the questionnaire in the Cavebath. The choosing of guests happened randomly. 199 questionnaires were correctly filled.